(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2016)
The annotated list of vascular plants of the one of the part of National Park "Oleshkivski sands" – the territory of Nova Kakhovka Ordinary Fish Hatchery – is presented. Flora of this area, which is about 200 hectares, has 197 species of vascular plants of 159 generas, 49 families and 4 departments. On the territory of Ordinary Fish Hatchery there are 7 rare vascular plant species which are included in the IUCN Red List, the European Red List, Red Data Book of Ukraine and Red List of Kherson region.